Financial Literacy of Bidikmisi Scholarship Recipient Students - Kurniadi, Romi; Suarman, Suarman; Syahza, Almasdi (FKIP - Universitas Riau, 2019)
This study aims to analyze the level of financial literacy of Bidikmisi scholarship recipients in the Teacher Training and Education Faculty of the University of Riau. This study involved 178 students as samples taken from a population of 630 students using the Cochran sampling technique. This research is a survey research. Data obtained through tests were analyzed descriptively. The results of the study show that the financial literacy of the Bidikmisi Scholarship recipient students is in the literate category. Financial knowledge related to basic personal finance is in the well literate category, financial management knowledge is in the literate category, knowledge of debt and credit is in the well literate category, knowledge related to savings and investment is in the unliterate category, and knowledge of risk management is in the unliterate category.